Study on the Component-Based Model of an All-Welded Beam-Column Connection for Progressive Collapse Analysis - Fuzhe Xie; Wenyuan Liu; Bin Gu; Hai Qian (Advances in Civil Engineering)
The mechanical behavior of all-welded beam-column connections of steel frames during progressive collapse was numerically studied using finite element simulations. The validation of the numerical model was based on a previous test model. The analysis results indicated that the stiffness of the all-welded beam-column connection in the elastic-plastic stage was mainly provided by the shear stiffness of the panel zone, and the axial compression on the column had a substantial impact on the capacity and ductility of the all-welded beam-column connection. An improved component-based model of the all-welded beam-column connection was proposed. To verify the accuracy of the proposed model, a beam-column assembly with an all-welded connection was established and the influence of the catenary action, column axial compression, beam-column stiffness ratio, and dynamic performance was parametrically analyzed. The validation results showed that the proposed model was able to simulate the behavior of all-welded beam-column connections at large structural deformation.